MORPHOLOGY AND MORPHOMETRIC FEATURES OF THE LARGE INTESTINE IN THE OFFSPING BORN FROM MOTHERS WITH DIABETES MELLITUS (EXPERIMENTAL STUDY) - Ernazar Kalmurzaev; Dilorom Adilbekova (Central Asian Journal of Medicine, 2025)
The experiment was conducted on 30 female laboratory rats, divided into two groups: control (n=15) and experimental (n=15). In the experimental group animals, diabetes mellitus was modeled by intravenous administration of alloxan in citrate buffer once intraperitoneally at a rate of 11 mg/100 g of weight. Hyperglycemia (>15 mmol/l) was confirmed using a glucometer. After confirmation of diabetes, the females were mated with healthy males. The colon was fixed in 10% formalin solution, histologically processed and stained with hematoxylin and eosin. Morphometric analysis included measuring the thickness of the mucous, submucous and muscular layers, the height of the crypts, and counting the number of goblet cells. The results of the study showed that the offspring born to mothers with diabetes have significant changes in the structure of the colon. The thickness of the mucous layer was reduced by 18% (p<0.05), the muscular layer — by 12% (p<0.05) compared to the control group. The height of the crypts decreased by 15% (p<0.05), indicating a violation of the epithelial regeneration processes. The number of goblet cells in the mucous membrane was significantly less (by 22%, p<0.01), which may indicate a decrease in the secretory function. Histological analysis revealed signs of disorganization of the epithelial layer, an increase in the intercellular space and a decrease in the density of cellular elements. Discussion of the results suggests that the identified changes are associated with the negative effect of hyperglycemia on the processes of proliferation and differentiation of cells during intrauterine development. A decrease in the thickness of the colon wall layers and a decrease in the number of goblet cells may be due to a violation of the synthesis of proteins and lipids, as well as a change in the expression of genes regulating histogenesis. These morphological changes may underlie functional disorders such as decreased absorption capacity, impaired motility, and increased risk of developing inflammatory processes in the colon.